Susceptibility of leguminous green manure species to Rhizoctonia solani and Sclerotium rolfsii - Paula Júnior,Trazilbo José de (2011)
We studied the susceptibility of species used as green manure in common bean fields to root rot (Rhizoctonia solani) and southern blight (Sclerotium rolfsii). Seeds of Crotalaria breviflora, Canavalia ensiformis, Cajanus cajan, Dolichos lablab, Stizolobium cinereum, S. aterrimum, and the bean cvs. "Pérola", "Valente" and "Carnaval" were sown in soil infested by either R. solani AG-4 or S. rolfsii in greenhouse. The emergence of D. lablab seedlings in soil infested by R. solani dropped to 62%. C. breviflora, C. ensiformis and cv. "Valente" presented the lowest root rot severity. The pathogen S. rolfsii drastically reduced seedling emergence in all species; no C. cajan and S. cinereum seedling emerged. All plant species presented high southern blight severity. We conclude that leguminous crops are not suitable as green manure for areas of bean cultivation with high R. solani and S. rolfsii populations.